Effect of Pharmacological Pupil Dilatation on Angle Configuration in Untreated Primary Angle Closure Suspects: A Swept Source Anterior Segment Optical Coherence Tomography Study. Issue 7 (July 2020) - Narayanaswamy, Arun; Baskaran, Mani; Tun, Tin A.; Htoon, Hla M.; Aung, Tin
Abstract : Precis: Angle-closure worsens with pharmacological dilatation in about 50.0% of the subjects diagnosed as primary angle-closure suspects (PACSs). Purpose: The purpose of this study was to evaluate the changes in angle configuration with swept-source anterior segment optical coherence tomography before and after pharmacological pupil dilatation in untreated PACSs. Patients and Methods: A total of 106 subjects over the age of 50 years and diagnosed as PACSs were included in this cross-sectional cohort study. 360-degree scans of the angles were captured using swept-source optical coherence tomography before and 1 hour after pharmacological dilatation. The angle scans from swept-source optical coherence tomography were analyzed to calculate the iris-trabecular contact (ITC) index. The main outcome measure was to evaluate the change in ITC index after dilatation. Multivariate linear and logistic regression analysis were performed to identify factors influencing change of ITC index and to identify factors associated with increase in ITC index after dilatation. Results: Majority of subjects were Chinese (93.4%) and female (79.2%). The overall mean predilatation ITC index was 45.3% (±23.7) and postdilatation ITC index was 46.05% (±25.9) with a mean change of 0.78% (±16.5; P =0.62). Fifty-three eyes (50.0%) showed an increase in ITC index (angle narrowing) after dilatation. An increase in ITC index was associated with shallower anterior chamber depth (odds ratio: 0.18; 95% confidence interval: 0.04-0.77) and bigger lens vault (odds ratio: 14.31; 95% confidence interval: 1.55-132.34). Conclusions: Pharmacological pupil dilatation worsened angle closure in 50.0% of subjects with narrow angles. Shallower anterior chamber and bigger lens vault were associated with greater angle narrowing in these subjects.